2015
DOI: 10.3390/su7043637
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Challenges in the Adoption of Building Applied Photovoltaics in the Swedish Tenant-Owner Housing Sector

Abstract: Sweden has committed itself to comply with EU-directive 2009/28/EC on energy from renewable sources and 2012/27/EU on improvement in the efficiency of energy. Measures in the existing housing stock, such as installing photovoltaics (PV), provide a means of contributing to the goals above. The purpose of this paper is to study how the organization of property management and the decision-making structure in tenant-owner cooperatives (TOCs) in Sweden facilitates or hampers the adoption of large-scale residential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Sweden has a lower solar radiation compared with countries more in the south since the maximum insolation angle is only 58 degrees in the far south of Sweden. Still the annual solar influx in the southern half of Sweden is comparable to that in northern Germany and the potential is estimated at 10-40 TWh/year (Muyingo, 2015). Most Swedes live in the southern parts, 88% of the population.…”
Section: Introductionmentioning
confidence: 97%
“…Sweden has a lower solar radiation compared with countries more in the south since the maximum insolation angle is only 58 degrees in the far south of Sweden. Still the annual solar influx in the southern half of Sweden is comparable to that in northern Germany and the potential is estimated at 10-40 TWh/year (Muyingo, 2015). Most Swedes live in the southern parts, 88% of the population.…”
Section: Introductionmentioning
confidence: 97%
“…Bio-physical conditions were at times hindering projects. For instance, for reason of limited roof space [48] or suboptimal roof-orientation for solar PV panels [43,52], inadequate (existing) infrastructure for the installation of solar thermal systems [43], or unsuitability of a rural area to be connected to a district heating grid [53].…”
Section: Bio-physical Conditionsmentioning
confidence: 99%
“…Whereas, the project she studied in Sweden involved rich, but passive consumers. Secondly, the role of gender has been pointed out by Muyingo [48], who found that members of the boards of tenant-owner cooperatives were often older, wealthier, well-educated males; in total "fifty-five percent of the inhabitants in tenant-owner cooperatives were women, while 66 percent of the members of the executive boards and 80 percent of the chairpersons are men" [48] (p. 3658).…”
Section: Attributes Of the Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…First, the article focusses on an a case study of an empirical situation; hence methods such as life-cycle assessments, modelling and simulations were excluded. Second, articles were published between 1999 13 and July 2018 and cover case studies that took place after 1999. Third, the content of the publication deals with (smart) renewable energy infrastructure in local settings, that is at the city district level.…”
Section: Selection Criteriamentioning
confidence: 99%